Three Dimension (3D) Animation Video Development On Dental Care For Children - ali, azita; zulkifli, wahida afrina (Research and Innovation in Technical and Vocational Education and Training, 2021)
This study aims to develop 3D animated videos about dental care for children. This 3D animated video will give a proper understanding and consciousness toward children ages of five and six of brushing teeth to prevent infection that can increase the risk of infection or other illnesses. What is the right course of action that they need to take to prevent the infection. It uses Waterfall development model in process of designing and developing 3D animated. The model consists of six phases which are planning phase, analysis phase, design phase, development phase, implementation and testing phase and the last phase is maintenance phase. In this study, there were five (5) specialists consisting of two (2) dental professionals, two (2) lecturers with experience and expertise in creative multimedia and one (1) three-dimensional (3D) animation field. The instrument use for the research is the questionnaire and the research method use is survey method. The analyzed data found that the experts agreed on the content and interface of 3D animation of dental care for children. This 3D animated video can increase children's interest because of the realistic shape of the 2D animations on television. This 3D animated video helps the child learn about dental care and to provide awareness for this dental care. This 3D animated video also give a positive effect on communicating information more effectively and easily